FAKTOR PENYEBAB KARIES GIGI PADA ANAK USIA SEKOLAH DASAR DI INDRAMAYU: indonesia - Roifatun Nisa; sukhriyatun fitriyah (Jurnal Medika Hutama, 2021)
Teeth are part of the chewing apparatus in the digestive system in the human body. The main problem of children's oral health is dental caries. The dental disease that is often suffered by almost all Indonesians is dental caries. Generally, children entering elementary school age have a high risk of caries, because at this school age children usually like to snack on food and drink according to their wishes. This study aims to determine the relationship between knowledge, attitudes and actions about dental hygiene against dental caries in students at Indramayu Regency. This type of research is quantitative research with descriptive research methods. In this study, the time approach used was a cross sectional study. The sample in this study used a total sampling of 32 grade 1 students. The results showed pearson chi square dengan Asymp. Sig (2-sided) knowladgw sebesar 0.003, pearson chi square dengan Asymp. Sig (2-sided) attitudes sebesar 0.002, pearson chi square Asymp. Sig (2-sided) actions sebesar 0.000, so that it can be concluded a relationship between knowledge, attitudes and actions about dental hygiene against dental caries in students at Indramayu.